Peningkatan Kapasitas Bisnis Berbasis Komunitas dan Mitigasi Sampah melalui Produk Konversi pada Bank Sampah Sinar Berlian - Budiman, Eko Wahyu; Pitaloka, Dyah; Masrunik, Endah; Puspitorini, Palupi; Sunandes, Aris; Endrawati, Tri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This community service was carried out in Gedog Village, Blitar City. The purpose of the service was to increase the capacity of household waste management and waste mitigation through conversion products and community-based business management at the